ANALISIS AKUNTANSI TRANSAKSI MATA UANG ASING: STUDI STRATEGIS PADA PT MAYORA INDAH TBK - Yulinda, Isma; Hasibuan, Dini Nurbaiti; Lubis, Rizki Insan Fitriah; Azman Ilham; Nurlaila (Jurnal Nirta : Inovasi Multidisiplin, 2025)
Foreign currencies hold significant importance in the realm of international business. Cross-border transactions, which frequently involve the use of foreign currencies, are conducted by companies as a result of rapid globalization and the increasing pace of global trade activities. Utilizing foreign currencies provides benefits such as market expansion, risk diversification, and the optimization of business opportunities. The type of research employed in this study is descriptive qualitative. The findings indicate that the policy regarding the recording of foreign currency transactions in the financial statements of PT Mayora Indah Tbk is as follows: transactions conducted in foreign currencies are converted into Rupiah using the exchange rate at the time of the transaction. Monetary assets and liabilities denominated in foreign currencies at the end of the period are reported based on the average buying and selling exchange rates published by Bank Indonesia for the latest banking transactions in the given period. Additionally, exchange rate differences, whether gains or losses, are recognized in the income statement for the current period. The foreign currency accounting policy implemented by PT Mayora Indah Tbk complies with PSAK 10, although exchange rate fluctuations continue to have a significant impact on the financial statements. The practical implications of compliance with this standard and its influence on financial decision-making will be analyzed. It is expected that an understanding of foreign currency accounting will enhance the quality and credibility of corporate financial statements in the global market.